META, GOOGLE, TIKTOK VA UNUTILISH HUQUQI: XUSUSIY KORPORATSIYALAR SHAXS DAXLSIZLIGINING KALITIMI? - Saparbayeva Maftuna Ikrom qizi (TADQIQOTLAR, 2026)
This article analyzes the relationship between the circulation of personal data on Meta, Google, and TikTok platforms and the practical enforcement of the right to be forgotten. The study draws on normative-legal and comparative approaches. The findings demonstrate that platform design, indexation mechanisms, and content replication significantly constrain the effective realization of the right to erasure. The scientific contribution lies in clarifying the criteria for corporate governance in the context of personal data protection.